Pengaruh Indikator Keuangan Terhadap Pertumbuhan Ekonomi Sektor Industri Pengolahan di Provinsi Jawa Tengah - Tulus Tulus; Abdul Aziz Ahmad; Suharno Suharno (Ekonomis: Journal of Economics and Business, 2020)
The number of industries in Central Java Province has experienced a significant increase, however, economic growth in the of the manufacturing sector is experiencing a slowdown. This study aims to analyze the effect of processing industry credit, working capital credit, investment credit, regional minimum wages and investment on the economic growth of the manufacturing sector in Central Java Province in 2011-2018. The data analysis technique used multiple linear regression with panel data with eviews sofware . The results showed that working capital credit has a positive and significant effect on economic growth in the of the manufacturing sector in Central Java Province in 2011-2018. The regional minimum wage has a negative and significant effect on the economic growth of the of the manufacturing sector in Central Java Province in 2011-2018. Processing industry credit, investment and investment credit not a significant on economic growth of the of the manufacturing sector in Central Java Province in 2011-2018. This research implies the need to increase working capital credit distribution and  the need to necessary to determine the ideal UMR.